2020
DOI: 10.1175/jamc-d-19-0135.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Wind Turbine Array Downstream Effects to the Parameterization Used in WRF

Abstract: The Weather Research and Forecasting (WRF) Model has been extensively used for wind energy applications, and current releases include a scheme that can be applied to examine the effects of wind turbine arrays on the atmospheric flow and electricity generation from wind turbines. Herein we present a high-resolution simulation using two different wind farm parameterizations: 1) the “Fitch” parameterization that is included in WRF releases and 2) the recently developed Explicit Wake Parameterization (EWP) scheme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 56 publications
(55 reference statements)
8
22
0
Order By: Relevance
“…Lower mean wind speeds are simulated for all heights during the summer months. This is consistent with the seasonality observed capacity factors for wind farms within Iowa that also exhibit a summer minimum [54]. Monthly mean wind speed profiles also imply lower shear during summer (Figure 3b).…”
Section: Wind Speed Profiles and Reusupporting
confidence: 83%
See 1 more Smart Citation
“…Lower mean wind speeds are simulated for all heights during the summer months. This is consistent with the seasonality observed capacity factors for wind farms within Iowa that also exhibit a summer minimum [54]. Monthly mean wind speed profiles also imply lower shear during summer (Figure 3b).…”
Section: Wind Speed Profiles and Reusupporting
confidence: 83%
“…In the summer months when conditions are most unstable (convective) and wind speeds are lowest [46], the eastern sites tend to experience high shear more frequently. The regional flow is generally dominated by southeasterly and southwesterly flow in winter and spring and dominated by southwesterly flow in summer [54]. The LLJ is more frequently associated with north/south wind directions and is more common in the northeast of the domain in spring [31] and may account for the high frequency of extreme shear in March and at night.…”
Section: Shear Across the Rotor Planementioning
confidence: 98%
“…Besides the different magnitudes, the spatial distribution of TKE also differs between the WFPs. The Fitch approach shows high TKE values within the farm at all levels, while the EWP approach shows a reduction below the rotor due to the extraction of kinetic energy and an increase downwind and above (Volker et al 2015;Shepherd et al 2020). Higher TKE values at the upper parts and above the rotor agree better with lidar observations (Lee and Lundquist 2017b) and LES results (Porté-Agel et al 2020).…”
Section: Impacts On Turbulence Kinetic Energymentioning
confidence: 58%
“…3.2.2). The recovery length has been found to be shorter for the EWP parametrization than for the Fitch parametrization over land (Pryor et al 2018a(Pryor et al , 2020Shepherd et al 2020), whereas over water Volker et al (2015) found the opposite in ideal simulations. An analysis of in situ aircraft measurements indicates that wake recoveries are for all stability conditions mostly exponential but can also be approximately linear (Cañadillas et al 2020).…”
Section: Impacts On Wind Speedmentioning
confidence: 90%
See 1 more Smart Citation